Regional circadian period difference in the suprachiasmatic nucleus of the mammalian circadian center. Issue 6 (22nd July 2013) - Koinuma, Satoshi; Asakawa, Takeshi; Nagano, Mamoru; Furukawa, Keiichi; Sujino, Mitsugu; Masumoto, Koh‐Hei; Nakajima, Yoshihiro; Hashimoto, Seiichi; Yagita, Kazuhiro; Shigeyoshi, Yasufumi
Abstract: The suprachiasmatic nucleus (SCN) is the mammalian circadian rhythm center. Individual oscillating neurons have different endogenous circadian periods, but they are usually synchronized by an intercellular coupling mechanism. The differences in the period of each oscillating neuron have been extensively studied; however, the clustering of oscillators with similar periods has not been reported. In the present study, we artificially disrupted the intercellular coupling among oscillating neurons in the SCN and observed regional differences in the periods of the oscillating small‐latticed regions of the SCN using a transgenic rat carrying a luciferase reporter gene driven by regulatory elements from a per2 clock gene ( Per2 ::dluc rat). The analysis divided the SCN into two regions – a region with periods shorter than 24 h (short‐period region, SPR) and another with periods longer than 24 h (long‐period region, LPR). The SPR was located in the smaller medial region of the dorsal SCN, whereas the LPR occupied the remaining larger region. We also found that slices containing the medial region of the SCN generated shorter circadian periods than slices that contained the lateral region of the SCN. Interestingly, the SPR corresponded well with the region where the SCN phase wave is generated. We numerically simulated the relationship between the SPR and a large LPR. A mathematical model of the SCN based on our findings faithfully reproduced the kinetics of the oscillators in the SCN in synchronized conditions, assuming the existence of clustered short‐period oscillators. Abstract : We disrupted the intercellular coupling among oscillating neurons in the suprachiasmatic nucleus (SCN), the mammalian circadian center. The treatment by forskolin divided the SCN into two regions: A region with periods shorter than 24 h (SPR) and another with periods longer than 24 h (LPR). The SPR corresponded well with the region in which the SCN phase wave is generated. A numerical simulation suggested that the coexistance of SPR and LPR generates the phase wave in the SCN.